1987
DOI: 10.1016/s0006-3495(87)83414-8
|View full text |Cite
|
Sign up to set email alerts
|

Picosecond time-resolved fluorescence of ribonuclease T1. A pH and substrate analogue binding study

Abstract: The tryptophyl fluorescence of ribonuclease T1 decays monoexponentially at pH 5.5, tau = 4.04 ns but on increasing pH, a second short-lived component of 1.5 ns appears with a midpoint between pH 6.5 and 7.0. Both components have the same fluorescence spectrum. Acrylamide quenches both fluorescence components, and the short-lived component is quenched fivefold faster than the predominant long component. Binding of the substrate analogue 2'-guanylic acid at pH 5.5 quenches the fluorescence by 20% and introduces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
52
1

Year Published

1988
1988
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(60 citation statements)
references
References 34 publications
7
52
1
Order By: Relevance
“…Table 2 (Table 2). They are, however, similar to the two lifetimes of 3.78 ns (amplitude = 89%) and 1.5 ns that are found in the native native state of the wild-type protein at pH 8 and 20 "C (Chen et al, 1987). The existence of two fluorescence lifetimes of Trp 59 at the stage of the intermediate may indicate that the structure of the intermediate is not as rigid as the native structure and thus the fluorophore can exist in two different conformations.…”
Section: Fluorescence Of the Folding Intermediatesupporting
confidence: 78%
See 2 more Smart Citations
“…Table 2 (Table 2). They are, however, similar to the two lifetimes of 3.78 ns (amplitude = 89%) and 1.5 ns that are found in the native native state of the wild-type protein at pH 8 and 20 "C (Chen et al, 1987). The existence of two fluorescence lifetimes of Trp 59 at the stage of the intermediate may indicate that the structure of the intermediate is not as rigid as the native structure and thus the fluorophore can exist in two different conformations.…”
Section: Fluorescence Of the Folding Intermediatesupporting
confidence: 78%
“…This is consistent with the molecular environment of Trp 59, which is completely buried in the hydrophobic core of native RNase T1. (Chen et al, 1987;Gryczynski et al, 1988) and probably originates from two distinct conformations of Trp 59 (Chen et al, 1987). Presumably, Trp 59 of (S54G,P55N)-RNase T1 can also exist in at least two distinct conformations at the stage of the folding intermediate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The difference in the xo reflects different protein concentrations and hence different solution viscosities in both samples. The values obtained by the NMR approach are well within the range of correlation times of RNase T1 obtained from fluorescence decay measurements (Eftnik, 1983;Lakowicz et al, 1983;James et al, 1985;Chen et al, 1987).…”
Section: Relaxation Data and Dynamical Parameterssupporting
confidence: 74%
“…Long before however, the two lifetimes had been proposed to originate from two conformers of the copper binding site which interact differently with the single Trp rotamer [48]. The fluorescence decay of ribonuclease T1 changes from monoexponential at low pH to bi-exponential under slightly destabilizing conditions like high pH, high temperature or in the presence of denaturant [49,50]. Still, a molecular mechanics study showed the existence of quasi-one Trp59 rotamer [51].…”
Section: The Rotamer Hypothesis and Its Fatementioning
confidence: 99%